Engineering Scheme Decision System Integrating Case Reasoning and BIM Technology - Qi Zhang (IEEE Access)
To solve the problem of lack of science and poor reusability of experience in traditional engineering scheme decision-making, which leads to the increase of time and cost of pre-decision-making, the study first uses case-based reasoning and ontology to construct a solution library for engineering solution decision-making system, and standardizes the cases using methods such as eigenfrequency. In addition, a retrieval mechanism based on residual similarity is designed to achieve effective retrieval of similar cases. The experiment outcomes denoted that the resource utilization rate of the traditional scheme was 75% before implementation, but decreased to 72% after implementation, a decrease of 3%. The resource utilization rate of the decision-making system scheme was 75% before implementation, and increased to 80% after implementation, an increase of 5%. The results indicated that the decision system scheme designed by the research performed better in terms of resource utilization, could more efficiently utilize resources, and reduce waste. The average decision accuracy of integrating CBR and BIM systems was 92%, significantly higher than the 84% of traditional decision systems. The CBR technology improved the scientificity and reliability of decision-making through continuous updating and optimization of the case library.